1987
DOI: 10.1149/1.2100812
|View full text |Cite
|
Sign up to set email alerts
|

Gettering of Copper in Silicon‐on‐Insulator Structures Formed by Oxygen Ion Implantation

Abstract: Copper is shown to be inadvertently introduced as an impurity during the formation of silicon-on-insulator structures by high fluence oxygen implantation. Postimplantation annealing causes the copper to diffuse from the silicon surface through the oxide and be preferentially gettered to dislocations that originate at the oxide-silicon substrate interface. The concentration of copper in the silicon surface layer is reduced by a factor of two, and no copper remains in the buried oxide layer. Sufficient gettering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Similar dopant distributions were also observed in gettering experiments. 30,31 In a previous publication, we have proposed a link between vacancy injection and substrate consumption. 10 We believe that since arsenic diffusion is enhanced by the vacancy injection at the interface, arsenic atoms can travel into the TiSi 2 even more effectively and reach the TiSi 2 surface where they occupy a fraction of the adsorption sites which would otherwise be available for SiH 4 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Similar dopant distributions were also observed in gettering experiments. 30,31 In a previous publication, we have proposed a link between vacancy injection and substrate consumption. 10 We believe that since arsenic diffusion is enhanced by the vacancy injection at the interface, arsenic atoms can travel into the TiSi 2 even more effectively and reach the TiSi 2 surface where they occupy a fraction of the adsorption sites which would otherwise be available for SiH 4 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Cu can diffuse through the BOX layer of SIMOX at elevated temperature. [5][6][7] However, the BOX layer in BESOI and bonded/ion-cut SOI is much denser than that in SIMOX.…”
Section: Introductionmentioning
confidence: 99%